Problematika Penerapan Literasi Di Sekolah Dasar Negeri 067980 Medan Denai - Khansa Nabila; Putri Enjelita S; Rina Wulan I.S.N; Tarisya Putri S.P (Jurnal Bintang Pendidikan Indonesia, 2024)
The literacy problem is one of the problems that needs special attention from Indonesian society. Literacy in elementary schools (SD) is very important because it is the foundation for students to develop reading, writing and arithmetic skills. Therefore, the aim of this research is to determine the problems in implementing literacy, especially at SDN 067980 Medan Denai. The method used in this research is descriptive qualitative research using a case study design. The research results show that the problems in implementing literacy are; (1) Students at SDN 067980 Medan Denai are less interested and still do not understand vocabulary and are not fluent in reading (2) Facilities at SDN 067980 Medan Denai are still inadequate for student literacy activities so that the impact on student learning outcomes is not increased (3) Lack of media supports both digital and non-digital used by teachers at SDN 067980 Medan Denai.